2009
DOI: 10.1097/pcc.0b013e3181a7045c
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter cohort study of in-hospital pediatric cardiac arrest*

Abstract: Objectives (1) Describe the clinical characteristics, hospital courses and outcomes of a cohort of children cared for within the Pediatric Emergency Care Applied Research Network (PECARN) who experienced in-hospital cardiac arrest with sustained return of circulation between July 1, 2003 and December 31, 2004, and (2) identify factors associated with hospital mortality in this population. These data are required to prepare a randomized trial of therapeutic hypothermia on neurobehavioral outcomes in children af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(135 citation statements)
references
References 40 publications
5
122
1
6
Order By: Relevance
“…8,14 Hastane içi çocukluk dönemi arrestlerin sonuçlarının son 10 yılda belirgin olarak iyiye doğru gittiği, bu olguların 2001 yılından 2009 yılına dek hastaneden taburcu olma oranlarının %24'den %39'a yükseldiği gösterilmiştir.…”
Section: çOcuklarda Hastane Içi Ve Dışı Arrestlerin Sonuçlarıunclassified
“…8,14 Hastane içi çocukluk dönemi arrestlerin sonuçlarının son 10 yılda belirgin olarak iyiye doğru gittiği, bu olguların 2001 yılından 2009 yılına dek hastaneden taburcu olma oranlarının %24'den %39'a yükseldiği gösterilmiştir.…”
Section: çOcuklarda Hastane Içi Ve Dışı Arrestlerin Sonuçlarıunclassified
“…The groundwork for this study has been well built. Three large, retrospective cohort studies that included patients from 15 hospitals affiliated with the Pediatric Emergency Care Applied Research Network have examined the outcome and identified risk factors associated with poor outcome for both in-hospital and out-of-hospital pediatric cardiac arrest [161][162][163][164][165][166][167][168][169][170][171]. Surveys from the United Kingdom and the United States have demonstrated both variability in the practice of cooling, and a widespread willingness and interest in a randomized controlled trial to study its use [172,173].…”
Section: Advances In Cerebral Resuscitation In Childrenmentioning
confidence: 99%
“…However, mortality (52%) and morbidity remain high despite advances in resuscitation training, technology and treatment (Tibballs et al, 2005). The devastating physical consequences of deterioration leading to cardiopulmonary arrest are well documented (Meert et al, 2009), as are the psychological effects that emergency admission to the Paediatric Intensive Care Unit (PICU) has on the family (Balluffi et al, 2004). There are significant additional financial costs to the National Health Service of 'failing to rescue' deteriorating children in hospital (Duncan and Frew, 2009).…”
Section: Introductionmentioning
confidence: 99%